The effect of service quality, perceived value, and customer trust towards customer loyalty on online transportation Gojek in Surabaya - Anandya, Dudi; Kevin, Kevin (Journal of Management and Business, 2021)
This study aims to analyze several factors that affect customer loyalty GoRide and GoCar in Surabaya. Several variables such as service quality, perceived value, and customer trust are examined in this study to see their effect on customer loyalty. This research is useful for Gojek in order to compete by increasing the customer loyalty that Gojek has. The research data collection was carried out by distributing questionnaires to 200 GoRide and GoCar customers in Surabaya. The sampling technique used in this research is non-probability sampling with a purposive sampling method. The criteria for respondents are Gojek customers (GoRide and GoCar) who still use the GoRide and GoCar applications, who have used the GrabBike and GrabCar applications, and are domiciled in Surabaya. The results of the data were collected and analyzed using the SEM (Structured Equation Modeling) method with the help of the SPSS AMOS 24 software. In this study, the relationship between service quality and perceived value are tested, service quality to customer loyalty, service quality to customer trust, value perceived customer loyalty, and customer trust on customer loyalty. The results of this study indicated that service quality has a positive and significant effect on perceived value and customer trust, but has no effect on customer loyalty. Perceived value considered to have a positive effect on customer loyalty. Customer trust has no effect on customer loyalty.